Why we celebrate St. Patrick's Day : everything to know about your favorite holiday - O'Brien, John, Jr (Callisto Publishing, an imprint of Sourcebooks, 2025)
"St. Patrick's Day is about more than just shamrocks and leprechauns! This engaging nonfiction book for kids explains the history, traditions, and customs of St. Patrick's Day-and includes interactive activities that encourage kids to celebrate at home or in their communities"--